The Challenges of the Oil Spill Preparedness and Responses - Ishak, I.C. (Springer Science and Business Media Deutschland GmbH, 2021)
Once an oil spill incident happens, it produces serious long-term effects on environmental, social, economics, marine ecosystems, coastal communities, and human life. Thus, this paper reviews the challenges on the oil spill incidents in Malaysia faced by main government agencies such as the Marine Department, Department of Environment, and a key player private organization named PIMMAG. The reviews are from related journal, articles, and other online references, respectively. It is vital to analyze the challenges in the oil spill management as Malaysia is facing oil spill cases. The findings disclosed that the main challenges are human mobility, miscommunication, insufficient equipment, and unknown sources of the oil spill incidents. Â© 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.